Virtual attractors, actual assemblages: How Luhmann's theory of communication complements actor-network theory - Ignacio Farías (European Journal of Social Theory, 2014)
This article proposes complementing actor-network theory (ANT) with Niklas Luhmann's communication theory, in order to overcome one of ANT's major shortcomings, namely, the lack of a conceptual repertoire to describe virtual processes such as sense-making. A highly problematic consequence of ANT's actualism is that it cannot explain the differentiation of economic, legal, scientific, touristic, religious, medical, artistic, political and other qualities of actual entities, assemblages and relationships. By recasting Luhmann's theory of functionally differentiated communication forms and sense-making as dealing with different types of virtual attractors calling for actualizations in concrete assemblages, I propose a symmetrical understanding of societal differentiation processes as based on the co-production of virtual attractors and actual assemblages.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; actor-network theory; differentiation; sense-making; social systems theory; symmetry